Identifications of Counselor Ideal Characters based on Hermeneutics Analysis of Ki Hadjar Dewantara’s Criticism Concept - Bakhrudin Habsy (KONSELOR, 2026)
Ki Hajar Dewantara is recognised as the Father of National Education and a National Hero of Indonesia. He established the Taman Siswa educational movement rooted in the principles of the Indonesian nation, aiming to enhance the dignity of the state and its people for the benefit of humanity globally. This qualitative research utilised a hermeneutic methodology to interpret Javanese literary traditions, particularly collections of Serat (manuscripts) and the aphoristic teachings of Ki Hajar Dewantara, and to express their meanings through systematic analysis. The researchers identified and developed the ideal traits of counsellors within the framework of Ki Hajar Dewantara’s philosophical framework. The findings demonstrate a clear, mutually supportive connection among the ideal qualities of counsellors, counselling communication techniques, and Ki Hajar Dewantara’s educational philosophy.